PHYSICOCHEMICAL PROPERTIES OF ALOE VERA GEL AND ITS UTILIZATION IN PREPARING SYNBIOTIC FERMENTED MILK WITH Bifidobacterium Lactis BB-12 - M. A. M. Alhamid; A. J. AL Mousawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate the physicochemical structure of fresh and dried Aloe Vera gel (AVG) and its adequacy as a prebiotic in the preparation of Synbiotic fermented milk with Bif. Lactis BB-12, in addition to its effect on the survival of these bacteria during 28 days of cold storage. The results indicated that the yield of the gel was % 64.56±1.157, and the moisture content, total solids (TS) and total soluble solids (TSS) in the fresh gel were % 98.23±0.0816, %1.777±0.0103 and % 1.56±0.0816 respectively. The pH of fresh and dried gel was 4.48±0.0105 and 4.63±0.01, respectively, meanwhile the acidity was 0.083±0.00121 and 0.058±0.0083, respectively (expressed as malic acid). Addition of 0.03% , 0.05% of dried and 3% ,5% of fresh AVG to treatments under study which represented as B1, B2, B3, and B4 respectively, reduced the generation time (GT) to 71.91, 68.49, 80.14 and 95.17 min, respectively as compared to that of the control treatment B0 (AVG free), which was 112.52 min. The pH value decreased in treatments B0, B1, B2, B3, and B4 to 4.45, 4.41, 4.36, 4.39 and 4.38, respectively, as the acidity increased to 1.13, 1.18, 1.26, 1.20 and 1.21%, respectively.